Hubungan Gaya Belajar dan Hasil Belajar Fiqih di MTsN 16 Jombang - Nurul Mutamimatul Husna; Wahyudi Wahyudi; Mohammad Saat Ibnu Waqfin (ANWARUL, 2026)
Fiqh learning, particularly the topic of prayer, plays an important role in shaping students’ understanding and practice of worship. However, in learning practice, differences in difficulties and learning outcomes among students are still found, which are presumed to be related to variations in learning styles. This study aims to determine students’ learning styles, Fiqh learning outcomes on the topic of prayer, and the relationship between learning styles and learning outcomes among Grade VII students at MTsN 16 Jombang. This study used a quantitative approach with a descriptive correlational design and involved 21 students as the sample. Data were collected through a learning style questionnaire consisting of 15 statement items and a learning outcome test comprising 12 multiple-choice questions and 10 essay questions. The data were analyzed using descriptive analysis, the Shapiro–Wilk normality test, the Levene Test for homogeneity, and the Pearson Product Moment correlation test. The results showed that students’ learning styles were diverse, with a dominant tendency toward the kinesthetic learning style. Fiqh learning outcomes on the topic of prayer obtained an average score of 78.90. The correlation test results showed a value of r = –0.013 with Sig. = 0.957 (p > 0.05), indicating that there was no significant relationship between learning styles and Fiqh learning outcomes on the topic of prayer among Grade VII students at MTsN 16 Jombang. Thus, H₀ was accepted and Hₐ was rejected. The conclusion of this study affirms that learning style is not the main factor influencing Fiqh learning outcomes on the topic of prayer. These findings imply the need for teachers to pay attention to other factors, such as learning motivation, discipline, interest, and learning strategies, in efforts to improve students’ learning outcomes.